Implementasi P5 kurikulum merdeka sebagai pembentukan karakter beriman siswa di SMPN Satu Atap Cibitung Bekasi - Rosfiani, Okta; Ramadhanti, Elsa; Lutfiyanti, Azizah; Heryawan, Zaidan Nur; Manal, Muhammad Sahlul; Hermawan, Cecep Maman (COLLASE (Creative of Learning Students Elementary Education), 2025)
This research discusses the implementation of the Pancasila Student Profile Strengthening Project (P5) in the Merdeka Curriculum at SMPN Satu Atap Cibitung Bekasi with a focus on building students' faith-based character. The introduction emphasizes the importance of P5 as a means to strengthen religious values in education, creating a generation of students who not only excel academically but also have faith-based character. The purpose of the study is to evaluate the effectiveness of P5 in developing students' religious character as well as identifying challenges and supporting factors in its implementation. The case study was conducted at SMPN Satu Atap Cibitung with a qualitative method, combining observation, and document study with the school. The results show that P5 contributes significantly to the formation of students' religious character, although there are obstacles such as limited facilities and teachers' understanding. The main recommendation is to improve teacher competence and support adequate facilities to achieve optimal results.